Battery-grade iron phosphate as well as preparation method and application thereof

By reacting the waste iron phosphate waste slag in waste lithium iron phosphate batteries with acid solution, copper powder and iron powder, battery-grade iron phosphate, the problems of waste resources and environmental pollution in the recycling of waste lithium iron phosphate batteries are solved, and the problem of wasteful resources and environmental pollution in waste lithium iron phosphate batteries is achieved. High purity, low cost iron phosphate recovery and safe preparation process.

CN119218953APending Publication Date: 2024-12-31TIANQI LITHIUM GENESIS TECH (SHENZHEN) LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340244.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art cannot effectively recycle and utilize the iron phosphate waste slag in waste lithium iron phosphate batteries, resulting in waste of resources and environmental pollution, and there are safety hazards and environmental risks during the lithium extraction process.

Method used

By reacting the waste residue after lithium extraction of waste lithium iron phosphate with mixed acid solution and copper powder, adjusting the pH value and reacting with iron powder, iron phosphate dihydrate is produced, and battery-grade iron phosphate is obtained through calcination, reducing hydrogen production , improve operational safety and achieve high-value recycling of iron phosphate.

Benefits of technology

High purity recycling and low-cost preparation of iron phosphate are achieved, which reduces safety risks during the preparation process. The recycled copper powder and iron powder can be reused, in line with the principle of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059476030000101
    Figure BDA0005059476030000101
  • Figure BDA0005059476030000111
    Figure BDA0005059476030000111
  • Figure HDA0005059476040000011
    Figure HDA0005059476040000011
Patent Text Reader

Abstract

The invention discloses battery-grade iron phosphate as well as a preparation method and application thereof, and relates to the technical field of comprehensive utilization of resources. According to the preparation method of the battery-grade iron phosphate provided by the embodiment of the invention, under the condition that the preparation cost is not increased, the generation amount of hydrogen in the preparation process is reduced, and potential safety hazards are reduced; the prepared iron phosphate product is in a battery grade standard range, which shows that the recovery purity of the iron phosphate is high; in addition, copper powder and iron powder recycled in the preparation process can be recycled, and extra preparation cost cannot be increased. The prepared battery-grade iron phosphate is expected to be applied to preparation of lithium iron phosphate battery raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of comprehensive resource utilization, and in particular to a battery-grade iron phosphate and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate is a common cathode material widely used in lithium-ion batteries. With the rapid development of electric vehicles and renewable energy industries, the demand for lithium iron phosphate batteries is also growing. The level and trend of lithium iron phosphate recycling technology are of great significance for achieving resource recycling, reducing environmental pollution and reducing costs.

[0003] At present, the recycling of lithium iron phosphate in waste lithium-ion batteries is mainly done by leaching lithium from the waste lithium through a wet process and then adding carbonate to form high-value lithium carbonate for recycling. The treatment of the ferrophosphorus waste residue after lithium extraction is to form phosphate fertilizer, iron red and other products for utilization, or directly discard it; no matter which treatment method is used, it is impossible to achieve high-value utilization of the ferrophosphorus waste residue and it puts great pressure on environmental protection. Therefore, it is imperative to develop a green and efficient process for recycling the ferrophosphorus waste residue generated after lithium extraction from waste lithium iron phosphate materials with low operating risks.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a battery-grade iron phosphate and a preparation method and application thereof to solve the above-mentioned technical problems.

[0006] The present invention is achieved in that:

[0007] In a first aspect, an embodiment of the present invention provides a method for preparing battery-grade iron phosphate, which comprises:

[0008] The waste residue after lithium extraction from waste lithium iron phosphate, the mixed acid solution and the copper powder are reacted, and after the reaction is completed, the first solid-liquid separation is performed;

[0009] After adjusting the pH value of the solution after the first solid-liquid separation to 2.2-2.5, the solution is reacted with iron powder, and after the reaction, a second solid-liquid separation is performed;

[0010] After heating the solution of the second solid-liquid separation to 90°C-100°C, adding an oxidant and an acid solution to react, thereby obtaining ferric phosphate dihydrate;

[0011] The iron phosphate dihydrate is calcined to obtain battery-grade iron phosphate.

[0012] In a second aspect, an embodiment of the present invention provides a battery-grade iron phosphate prepared by the aforementioned preparation method.

[0013] In a third aspect, an embodiment of the present invention provides an application of battery-grade iron phosphate prepared by the aforementioned preparation method in the preparation of raw materials for lithium iron phosphate batteries.

[0014] The present invention has the following beneficial effects:

[0015] The method for preparing battery-grade iron phosphate provided in an embodiment of the present invention first adds copper powder and then iron powder without increasing the preparation cost, thereby reducing the amount of hydrogen generated during the preparation process and thereby reducing safety hazards; the prepared iron phosphate products are all within the battery-grade standard range, indicating that the recovered iron phosphate has a high purity; in addition, the copper powder and iron powder recovered during the preparation process can be recycled and reused without increasing additional preparation costs; the battery-grade iron phosphate prepared by the present invention is expected to be used in the preparation of raw materials for lithium iron phosphate batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is a process flow chart for preparing battery-grade iron phosphate. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] Chinese invention patent CN113912032A, the invention name is a method for recovering battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate battery positive electrode powder. The patent discloses: after adding acid to the iron phosphate slag after lithium leaching with lithium iron phosphate acid to dissolve it, add iron powder to remove Cu, add fluorine compounds to remove aluminum, and after obtaining a ferrous solution with low impurity content, add hydrogen peroxide to synthesize iron phosphate. Although this method can obtain lithium carbonate and iron phosphate at the same time, it has the disadvantage that the added iron powder will react with the acid leaching solution to release a large amount of hydrogen, which increases the risk of the entire process; secondly, the patent uses fluoride to remove aluminum from the ferrous solution. The fluoride used is toxic and harmful in itself, and there are risks when using it. When the fluoride is added to the acidic solution, HF will inevitably be generated, which is unfriendly to the environment and operators. Therefore, it is urgent to propose a green, efficient recovery and low-risk operation process process to recover the phosphorus iron waste slag produced after lithium extraction from waste lithium iron phosphate materials.

[0020] In a first aspect, an embodiment of the present invention provides a method for preparing battery-grade iron phosphate, which comprises:

[0021] The waste residue after lithium extraction from waste lithium iron phosphate, the mixed acid solution and the copper powder are reacted, and after the reaction is completed, the first solid-liquid separation is performed;

[0022] After adjusting the pH value of the solution after the first solid-liquid separation to 2.2-2.5, the solution is reacted with iron powder, and after the reaction, a second solid-liquid separation is performed;

[0023] After heating the solution of the second solid-liquid separation to 90°C-100°C, adding an oxidant and an acid solution to react, thereby obtaining ferric phosphate dihydrate;

[0024] The iron phosphate dihydrate is calcined to obtain battery-grade iron phosphate.

[0025] The waste residue after lithium extraction from waste lithium iron phosphate used in the embodiment of the present invention includes iron phosphate carbon residue.

[0026] It should be noted that iron phosphate carbon slag contains heavy metals and other pollutants. If not properly treated, it will pose a potential threat to the environment and human health. After proper treatment, it can be reused, which can not only realize the resource utilization of waste, but also create new economic growth points; in addition, it reduces dependence on natural resources and conforms to the principle of sustainable development.

[0027] Specifically, in an optional embodiment of the present invention, the waste residue is mixed with water to prepare a slurry according to a solid-liquid ratio of the waste residue to water of 1:(1-2.5). Further, the solid-liquid ratio of the waste residue to water is 1:2.

[0028] It should be noted that the setting of the solid-liquid ratio of waste residue and water can facilitate the rapid reaction of waste residue with mixed acid solution and copper powder. In other embodiments of the present invention, the order of adding water can be reasonably adjusted, such as mixing waste residue and copper powder first, and then adding water and mixed acid solution to react.

[0029] In an optional embodiment of the present invention, the molar ratio of waste residue and copper powder is 1:(0.45-0.65); specifically, mixed acid solution and copper powder are added to the prepared slurry for reaction, wherein the molar ratio of waste residue, mixed acid solution and copper powder is 1:(2-2.5):(0.53-0.58).

[0030] Specifically, the mixed acid solution is first added to the slurry for dissolution, and after the slurry is completely dissolved, copper powder is added for reaction. The addition of copper powder makes the Fe in the solution 3+ Convert to Fe 2+ At this time, the ions contained in the solution are PO4 3- , SO4 2- , Fe 2+ , Cu 2+ , H + .

[0031] The present invention adds copper powder instead of iron powder to the acid solution, thereby avoiding the iron powder from reacting with the acid after entering the acid solution, thereby releasing a large amount of hydrogen, which increases the risk of the entire process; the addition of copper powder makes the reaction milder, and no hydrogen is generated during the reaction, thereby improving the safety of the operation. In addition, if iron powder is added in this step, the iron powder will react with the phosphate in the solution to generate iron phosphate precipitation, which is removed in the form of filter residue, and the phosphate content in the solution will be impaired.

[0032] In an optional embodiment of the present invention, the mixed acid solution comprises sulfuric acid and phosphoric acid in a molar ratio of (1-1.5): 1. Further, the molar ratio of sulfuric acid to phosphoric acid is 1.3:1.

[0033] Specifically, the sulfuric acid used in the embodiment of the present invention is sulfuric acid with a mass concentration of 98%, and the phosphoric acid is phosphoric acid with a mass concentration of 85%. When the two acid solutions are mixed, sulfuric acid is slowly added to phosphoric acid, and stirring is performed while adding to avoid splashing and danger caused by excessively high local temperature when sulfuric acid is added. In addition, it should be noted that because the mass concentrations of the sulfuric acid and phosphoric acid used are both high, when the mixed acid solution is added to the slurry for dissolution reaction, it is necessary to slowly add and stir the mixed acid solution to avoid splashing of the mixed acid solution caused by excessively high local temperature of the reaction system, which is dangerous to the operator.

[0034] Sulfuric acid and phosphoric acid are mixed in a certain ratio to quickly dissolve the waste residue while providing an acidic environment for the reaction system. The amount of phosphoric acid added must be matched with the amount of subsequent iron powder supplement in a 1:1 ratio. This ratio setting can just completely convert the subsequent iron powder supplement into iron phosphate.

[0035] In an optional embodiment of the present invention, in order to make Fe in the solution 3+ Completely converted to Fe 2+ After adding copper powder, the reaction time is greater than 30min, and the amount of copper powder added is greater than the Fe content in the slurry. 3+ The amount should be slightly excessive to ensure that the Fe 3+ After the reaction is completed, solid-liquid separation is performed. In the embodiment of the present invention, solid-liquid separation is performed by filtering. It should be noted that in other embodiments of the present invention, other methods can be selected for solid-liquid separation according to actual needs, such as centrifugation.

[0036] It should be noted that if the amount of copper powder added is small, the separated solid will contain iron phosphate, reducing the subsequent yield of iron phosphate; if the amount of copper powder added is large, the amount of subsequent carbon powder and copper powder separation will increase, increasing the workload.

[0037] The solution after the first solid-liquid separation is an acid leaching solution, and its pH value is about 1.0 after testing; the solid after the first solid-liquid separation includes copper powder and carbon powder. In other embodiments of the present invention, the reaction time after adding copper powder can be reasonably adjusted according to the actual amount of raw materials used in the reaction.

[0038] It should be noted that copper powder and carbon powder can be separated by air separation or screening according to actual needs; the separated copper powder is collected and mixed with the copper powder collected in the subsequent process for use in the next reaction, saving the cost of raw material use.

[0039] In an optional embodiment of the present invention, the pH value of the solution after the first solid-liquid separation is adjusted to 2.2-2.5, and then reacted with iron powder, and a second solid-liquid separation is performed after the reaction is completed; wherein the substance for adjusting the pH value of the solution after the first solid-liquid separation is a carbonate; further, the carbonate is selected from any one of sodium carbonate and potassium carbonate.

[0040] It should be noted that the use of carbonate to adjust the pH of the solution after the first solid-liquid separation can reduce the amount of H + The concentration of the carbonate solution can avoid the danger of generating a large amount of hydrogen after the subsequent addition of iron powder. On the other hand, the carbonate solution is weakly alkaline, which can avoid the hydroxyl ions introduced by the strong alkaline solution to the Fe in the solution of the first solid-liquid separation. 2+ , Cu 2+ A precipitation reaction occurs.

[0041] The mass concentration of carbonate is not particularly limited in the present invention, and it can be reasonably adjusted and replaced according to actual needs. Specifically in the embodiment of the present invention, a sodium carbonate solution with a mass concentration of 10% is used.

[0042] Specifically, a sodium carbonate solution with a mass concentration of 10% is added to the solution after the first solid-liquid separation, and its pH value is adjusted to 2.2-2.5. At this time, the solution includes phosphate, dihydrogen phosphate, copper phosphate, dihydrogen copper phosphate, dihydrogen cupric phosphate and ferrous phosphate. Then iron powder is added to react with Cu in the acid leaching solution. 2+ The amount of substance is (1-1.5): 1. The reaction time after the iron powder is added is greater than 30 minutes, and the specific time can be reasonably adjusted according to the amount of raw materials used.

[0043] It should be noted that the purpose of adding iron powder is to replace copper, and the amount of iron powder added only needs to completely replace the copper ions in the solution, that is, the amount of iron powder added only needs to be slightly excessive compared to the copper ions in the solution.

[0044] In an optional embodiment of the present invention, after the solution system reacts for 30 minutes, a second solid-liquid separation is performed by filtering. The solution components of the second solid-liquid separation include ferrous dihydrogen phosphate, which is used as a raw material for subsequent precipitation of ferric phosphate, and the solid of the second solid-liquid separation is a mixture of copper powder and iron powder.

[0045] It should be noted that the pH value of the solution is around 2.5 at this time, and the iron powder reacts with the solution to produce a trace amount of hydrogen after being added.

[0046] The solids from the second solid-liquid separation are separated physically, using a magnet to separate the copper powder and the iron powder, and then collected separately for later use. In other embodiments of the present invention, other suitable separation methods can be selected according to actual needs.

[0047] In an optional embodiment of the present invention, after the solution of the second solid-liquid separation is heated to 90° C.-100° C., an oxidant and an acid solution are added to react to obtain ferric phosphate dihydrate.

[0048] Furthermore, the oxidant added to the solution of the second solid-liquid separation is hydrogen peroxide, and the acid is sulfuric acid. The specific reaction is as follows:

[0049] Fe3(PO4)2+H2O2+H3PO4→FePO4(↓)+H2O+H +

[0050] Specifically, in the embodiment of the present invention, hydrogen peroxide with a mass concentration of 30% and sulfuric acid with a mass concentration of 10% are added to the solution of the second solid-liquid separation; the purpose of adding hydrogen peroxide for oxidation leaching is to further promote the formation of FePO4·2H2O and improve the Fe 2+ The precipitation conversion rate to FePO4. Among them, hydrogen peroxide and sulfuric acid are added to the second solid-liquid separation solution in parallel to react. The addition of sulfuric acid is to adjust the pH value of the system, and when the pH value is kept at 2, iron phosphate is precipitated to avoid excessive Al content in the product.

[0051] It should be noted that the use of hydrogen peroxide as an oxidant will not introduce impurities into the system, thereby avoiding affecting the purity of the subsequent lithium sulfate solution; temperature control is conducive to the synthesis of ferric phosphate dihydrate; the sulfate content in the synthesized ferric phosphate dihydrate is much higher than the battery grade standard, and it needs to be cleaned to remove excess sulfate.

[0052] In addition, in an optional embodiment of the present invention, hydrogen peroxide is introduced from the bottom of the solution system, which can increase the agitation of the solution, accelerate the reaction rate, and promote Fe 2+ On the other hand, it can increase the precipitation conversion rate to FePO4; on the other hand, it can prevent H2O2 from decomposing into oxygen at high temperature and escaping directly from the surface of the solution, thereby increasing the amount of H2O2 used.

[0053] The solution used in the cleaning operation of the embodiment of the present invention is water, and the type of water can be selected from pure water, deionized water, or ultrapure water according to actual needs. The number of cleaning times and the amount of water used are reasonably adjusted according to actual needs until the sulfate content in the solution meets the requirements of the battery grade standard.

[0054] Specifically in the embodiments of the present invention, water is added for each cleaning at a solid-liquid ratio of 1:20. It should be noted that after the slurry is filtered, the solution adheres to the solid surface, and the solid needs to be rinsed first. The purpose of eluting is to wash away this part of the high-concentration surface liquid to avoid excessive impurity ions in the stirring solution during subsequent stirring and washing, which increases the water consumption and workload; during the cleaning process, appropriate stirring can be performed to accelerate the sulfate ions on the solid surface to enter the cleaning solution and speed up the removal rate of sulfate ions. The standard for cleaning compliance is to detect the sulfate content in the solid product.

[0055] In an optional embodiment of the present invention, the cleaned ferric phosphate dihydrate is calcined at 550° C.-600° C. to obtain battery-grade iron phosphate.

[0056] It should be noted that high-temperature calcination is beneficial to the decomposition of sulfur-containing substances in the solid product; the calcination reaction time can be reasonably adjusted according to the actual amount of raw materials to be processed.

[0057] It has been determined that the content of each particle in the battery-grade iron phosphate prepared in the embodiments of the present invention is within the battery-grade standard range.

[0058] In a second aspect, an embodiment of the present invention provides a battery-grade iron phosphate prepared by the aforementioned preparation method.

[0059] In a third aspect, an embodiment of the present invention provides an application of battery-grade iron phosphate prepared by the aforementioned preparation method in the preparation of raw materials for lithium iron phosphate batteries.

[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0061] Example 1

[0062] This embodiment provides a battery-grade iron phosphate, the preparation method of which includes the following:

[0063] After the iron phosphate carbon slag is mixed with water at a solid-liquid ratio of 1:2 to form a slurry, a mixed acid solution of sulfuric acid and phosphoric acid is added to dissolve it. After the iron phosphate carbon slag is dissolved, copper powder is added and stirred for reaction for 30 minutes. After the reaction is completed, the first solid-liquid separation is performed by filtering. Among them, n (FePO4: H3PO4: H2SO4: copper powder) = 1: 1: 1.3: 0.55.

[0064] The solution of the first solid-liquid separation is an acid leaching solution, and the solid of the first solid-liquid separation is a mixture of carbon powder and copper powder, with only a small amount of copper powder. Among them, the copper powder and the carbon powder can be separated by air selection, and the copper powder is collected for later use.

[0065] 10% sodium carbonate solution was added dropwise to the solution of the first solid-liquid separation to adjust the solution pH to 2.5. Iron powder was then slowly added. n (iron powder: Cu in the acid leaching solution) 2+ )=1.1:1. The reaction was continued for about 30 minutes, and the second solid-liquid separation was performed.

[0066] The solution from the second solid-liquid separation is set aside; the solid from the second solid-liquid separation is copper powder and iron powder, with only a small amount of iron powder; the copper powder and the iron powder are separated by a magnetic bar and collected separately for later use.

[0067] After the second solid-liquid separation solution is heated to 95° C., 10% sulfuric acid solution and 30% hydrogen peroxide solution are added dropwise in parallel to maintain the pH of the system at 2 to synthesize ferric phosphate dihydrate.

[0068] The synthesized ferric phosphate dihydrate is stirred and washed three times (solid-liquid ratio = 1:20, the solution is water), and calcined at 600° C. for 3 hours to obtain battery-grade iron phosphate.

[0069] Example 2

[0070] This embodiment provides a kind of iron phosphate, and its preparation method comprises the following:

[0071] After the iron phosphate carbon slag is mixed with water at a solid-liquid ratio of 1:2 to form a slurry, a mixed acid solution of sulfuric acid and phosphoric acid is added to dissolve it. After the iron phosphate carbon slag is dissolved, copper powder is added and stirred for reaction for 30 minutes. After the reaction is completed, the first solid-liquid separation is performed. Among them, n (FePO4: H3PO4: H2SO4: copper powder) = 1: 1: 1.3: 0.4.

[0072] The solution of the first solid-liquid separation is an acid leaching solution, and the solid of the first solid-liquid separation is carbon powder.

[0073] 10% sodium carbonate solution was added dropwise to the solution of the first solid-liquid separation to adjust the solution pH to 2.5. Iron powder was then slowly added. n (iron powder: Cu in the acid leaching solution) 2+ )=1.1:1. The reaction was continued for about 30 minutes, and the second solid-liquid separation was performed.

[0074] The product system is subjected to a second solid-liquid separation, and the obtained second solid-liquid separation solution is used for standby; the solid of the second solid-liquid separation is a mixture of copper powder, a small amount of iron powder and iron phosphate. It should be noted that this part of iron phosphate and metal powder cannot be separated in a simple manner.

[0075] The second solid-liquid separation solution obtained by filtration was heated to 95° C., and then 10% sulfuric acid solution and 30% hydrogen peroxide solution were added dropwise in parallel to maintain the pH of the system at 2 to synthesize ferric phosphate dihydrate.

[0076] The synthesized ferric phosphate dihydrate was stirred and washed three times (solid-liquid ratio = 1:20, the solution was water), and calcined at 600° C. for 3 h to obtain ferric phosphate.

[0077] Comparative Example 1

[0078] This comparative example provides a battery-grade iron phosphate, the preparation method of which includes the following:

[0079] After the iron phosphate carbon slag is mixed with water in a solid-liquid ratio of 1:2 to form a slurry, a mixed acid solution of sulfuric acid and phosphoric acid is added to dissolve it. After the iron phosphate carbon slag is dissolved, iron powder is added and stirred for reaction for 30 minutes. After the reaction is completed, the first solid-liquid separation is performed. Among them, n (FePO4: H3PO4: H2SO4: iron powder) = 1: 1: 1.3: 0.9.

[0080] It should be noted that the above slurry reacted violently after the mixed acid solution was added, and a large amount of obvious bubbles were generated during the reaction.

[0081] The solution of the first solid-liquid separation is an acid leaching solution for standby use; the solid of the first solid-liquid separation is a mixture of carbon powder and iron powder.

[0082] After the solution of the first solid-liquid separation is heated to 95° C., 10% sulfuric acid solution and 30% hydrogen peroxide solution are added dropwise in parallel to maintain the pH of the system at 2 to synthesize ferric phosphate dihydrate.

[0083] The synthesized ferric phosphate dihydrate is stirred and washed three times (solid-liquid ratio = 1:20, the solution is water), and calcined at 600° C. for 3 hours to obtain battery-grade iron phosphate.

[0084] Test Example 1

[0085] This test example measures the content of each ion and the iron-phosphorus ratio in the process products of Examples 1-2 and Example 2 and the battery-grade iron phosphate prepared in Comparative Example 1, and its reference is HG / T4701-2014, wherein trace ions are measured using an inductively coupled plasma spectrometer ICP, iron is measured using a titration method, and phosphorus is measured using a gravimetric method. The relevant results are specifically shown in Table 1.

[0086] It should be noted that the process product of Example 2 refers to the situation where insufficient copper powder is added and part of the iron phosphate in the acid leaching solution cannot be reduced. This part of the iron phosphate will be directly precipitated during the process of adjusting the pH value with sodium carbonate, and the impurity content of this part of the iron phosphate will exceed the standard.

[0087] Table 1

[0088]

[0089]

[0090] It should be noted that "ND" in the table means that the data here cannot be measured.

[0091] As can be seen from Table 1, battery-grade iron phosphate was prepared in Example 1, Example 3 and Comparative Example 1. In Example 2, due to the low content of copper powder used, when the pH value of the solution of the first solid-liquid separation was adjusted with sodium carbonate, part of the iron phosphate was precipitated, and the contents of this part of iron phosphate, copper and aluminum increased significantly, wherein the copper content exceeded the range specified by the battery-grade standard, and the iron phosphate prepared thereby did not meet the battery-grade standard.

[0092] Although battery-grade iron phosphate can be synthesized in Comparative Example 1, the molar ratio of iron phosphate to iron powder is 1:0.9 in Comparative Example 1, and the molar ratio of iron phosphate to iron powder is 1:0.55 in Example 1. In Comparative Example 1, the consumption of iron powder comes from three parts: ① reduction of iron phosphate to ferrous phosphate, the ratio of this part of iron powder to iron phosphate is 0.5:1; ② iron powder and Cu in the acid leaching solution; 2+ Replacement reaction occurs. The ratio of the amount of iron to copper in the solid iron-phosphorus slag is about (35-40:1). 2+The ratio of iron powder to iron phosphate is (0.0125-0.0145):1. ③ The iron powder reacts with the acid solution, and the ratio of this part of iron powder to iron phosphate is (0.9-reduced iron powder-replaced Cu 2+ The ratio of iron powder to acid is about 0.05:0.4, that is, the amount of iron powder in Example 1 is reduced by 87.5% compared with that in Comparative Example 1. It can be seen from the above that 4 / 9 of the added iron powder reacts with the acid to produce hydrogen; similarly, it can be concluded that the ratio of iron powder reacting with the acid in Example 1 and Comparative Example 1 is about 0.05:0.4, that is, the amount of iron powder in Example 1 is reduced by 87.5% compared with that in Comparative Example 1. It can be seen that the amount of hydrogen produced in Example 1 is greatly reduced compared with Comparative Example 1.

[0093] Secondly, phosphoric acid and iron powder are added in both Example 1 and Comparative Example 1. However, the ratio of the amount of iron powder added in Example 1 to that in Comparative Example 1 is 0.55:0.9. The added iron powder and phosphoric acid eventually react to form an iron phosphate product, but the price of iron powder itself is relatively high, and this method of synthesizing iron phosphate is not economical.

[0094] In summary, in the preparation method of battery-grade iron phosphate provided by the present invention, the copper powder and iron powder recovered in the preparation process can be recycled and reused without increasing additional preparation costs; the amount of hydrogen generated in the preparation process is small, reducing safety hazards; in addition, the specific gravity of iron phosphate in the preparation process is low, which is conducive to cost savings.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing battery-grade iron phosphate, characterized in that: The preparation method comprises: The waste residue after lithium extraction from waste lithium iron phosphate, the mixed acid solution and the copper powder are reacted, and after the reaction is completed, the first solid-liquid separation is performed; After adjusting the pH value of the solution after the first solid-liquid separation to 2.2-2.5, reacting with iron powder, and performing a second solid-liquid separation after the reaction; After heating the solution of the second solid-liquid separation to 90° C.-100° C., adding an oxidant and an acid solution to react to obtain ferric phosphate dihydrate; The ferric phosphate dihydrate is calcined to obtain the battery-grade ferric phosphate.

2. The preparation method according to claim 1, characterized in that: The amount ratio of the waste slag to the copper powder is 1:(0.45-0.65).

3. The preparation method according to claim 1, characterized in that: The ratio of the amount of the waste residue, the mixed acid solution and the copper powder is 1:(2-2.5):(0.53-0.58); Preferably, the waste residue comprises iron phosphate carbon residue; Preferably, before adding the mixed acid solution, the waste residue is further mixed with water; the solid-liquid ratio of the waste residue to water is 1:(1-2.5).

4. The preparation method according to claim 3, characterized in that: The mixed acid solution includes sulfuric acid and phosphoric acid in a molar ratio of (1-1.5):

1.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the iron powder to the copper ions in the solution after adjusting the pH value is (1-1.5):1; Preferably, the solids from the first solid-liquid separation include copper powder and carbon powder.

6. The preparation method according to claim 1, characterized in that: The substance used to adjust pH is carbonate; Preferably, the carbonate is selected from any one of sodium carbonate and potassium carbonate.

7. The preparation method according to claim 1, characterized in that: The oxidant added to the solution of the second solid-liquid separation is hydrogen peroxide, and the acid is sulfuric acid; Preferably, the solids from the second solid-liquid separation include copper powder and iron powder.

8. The preparation method according to claim 1, characterized in that: The calcination treatment of the ferric phosphate dihydrate also includes washing; the washing is used to remove sulfate in the ferric phosphate dihydrate; Preferably, the temperature of the calcination treatment of ferric phosphate dihydrate is 550°C-600°C.

9. A battery-grade iron phosphate prepared by the preparation method according to any one of claims 1 to 8.

10. Use of battery-grade iron phosphate prepared by the preparation method according to any one of claims 1 to 8 in preparing raw materials for lithium iron phosphate batteries.